IMPACT OF RADIOLOGY PROTOCOLS ON RADIATION DOSE REDUCTION - Mousa Habqan Alshammari, Adel Zaid Alshammari, ‏Sultan Albishri Mutair Alshammari, ‏Zamil Saud Saad Altamimi, ‏Saleh Abdullah Almuzaini, ‏Dhari saleh alabidah, ‏Ghalib Salem Olyan Alshammari, ‏Abdulaziz Sunaidah Shaea Alsunaidah, ‏Mohammed Saleh Alhamdan,,; Dhari Labdan Enad Alshammari, ‏Abdullah Hamed M Albaqawi, ‏Abdullah khalaf Q. Alshammari, ‏ Mona manawr alshammari, ‏Mohammed Ghazzai Aleluwi, Nabit Saeid Alnabit, Maram Saleh Alkharisi Alshammari, Bayan Ahmed Mabrouk Al khrd, (Chelonian Research Foundation, 2022)
Image-guided radiation treatment (IGRT) has revolutionized radiotherapy by using imaging technologies for precise patient placement and target localization. The administration of the imaging dose may lead to an excessive amount of radiation being received by sensitive organs, which might possibly raise the risk of developing secondary malignancies. As a consequence, it is crucial to effectively control and regulate the dosage. We provide a concise overview of the radiation dosage received by patients undergoing radiotherapy (RT) as a consequence of various image guiding processes. Additionally, we provide a compilation of the average doses received by organs during the capture of MV and kV images. While the imaging dosage from modern kV acquisition technologies is often below this level, it is important to constantly use the ALARA principle in practice. Medical physicists should inform radiation oncologists about the imaging doses given to patients under their supervision. In order to effectively locate the target, it is necessary to balance the ALARA principle (As Low As Reasonably Achievable) with the need for accurate target localization. This involves managing the imaging dosage by carefully assessing and evaluating the risks and benefits to the patient. Keywords: Radiology, scan imaging, dose calculation, image-guided radiation treatment (IGRT).